Do New Mothers Understand the Risk Factors for Maternal Mortality?. Issue 4 (July 2018) - Logsdon, M. Cynthia; Davis, Deborah Winders; Myers, John A.; Masterson, Katlin M.; Rushton, Jeffrey A.; Lauf, Adrian P.
Abstract: Purpose: The purpose of this study was to describe new mothers' knowledge related to maternal mortality. Study Design and Methods: Using a cross-sectional design, new mothers were recruited from a postpartum unit of an academic health sciences center where the population was predominately low-income women. Before hospital discharge, they answered questions on their knowledge of potential postpartum complications that could lead to maternal mortality. Questions were based on recommendations from an expert nursing panel. Descriptive statistics were used for data analysis. Results: One hundred twenty new mothers participated. Results indicated that most new mothers knew that they should watch for heavy bleeding, a severe headache, and swelling after hospital discharge. However, fewer participants knew that a new mother could experience feelings that she could harm herself or her baby, have blood clots larger than a baby's hand, a temperature of 100.4 °F or higher, and odor with vaginal discharge. Courses of action new mothers would take if experiencing any of the warning signs included 18% of mothers would take no action, 76.7% would tell their boyfriend/husband/partner, 72.5% would inform their mother. Only 60% who would call the labor and delivery unit. Only 38% of the sample knew that pregnancy-related complications can occur for up to 1 year after birth, and 13% of mothers reported not knowing that complications can occur for up to 6 weeks postpartum. Clinical Implications: Our findings provide a foundation to enhance postpartum education for new mothers and their families and to potentially decrease rates of maternal mortality in the United States. Abstract : Maternal mortality is at an all time high in the United States and exceeds the rates in some developing countries. This study evaluated the knowledge of potentially life-threatening complications of childbirth in a sample of low-income new mothers during their postpartum hospitalization. Findings suggest we need to do much better on postpartum discharge teaching so new mothers know when to call their midwife, nurse practitioner, or physicians if postpartum complications occur during the first year after giving birth, so risks of maternal mortality can be decreased.